Ethnomathematics Exploration of The Taganing Musical Instrument - Rahmadani, Tasya; Reflina, Reflina (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Education and culture are habits that are interconnected with human life. In education, culture can be used as a medium of learning both in schools and in culture itself. North Sumatra has various unique ethnicities, one of which is the Toba Batak which must be preserved and passed down from generation to generation. One of the Toba Batak cultures is the Taganing , a traditional musical instrument consisting of five drums with different heights and diameters that produce different tones and are played by two players. The purpose of this study is to explore what mathematical concepts exist in the Taganing  musical instrument so that it can be implemented in learning mathematics.This research uses qualitative with ethnography methods with research instruments in the from of observation and documentation. The results of this study indicate that the Taganing  musical instrument contains the concept of geometry and integral calculus.